Imprints of evolution on the internal kinematics of Globular Clusters. Issue Volume 14:Issue S351(2019) (May 2019) - Watkins, Laura L.; van der Marel, Roeland P.; Bellini, Andrea; Libralato, Mattia; Anderson, Jay
Abstract: Globular clusters are collisional systems, meaning that the stars inside them interact on timescales much shorter than the age of the Universe. These frequent interactions transfer energy between stars and set up observable trends that tell the story of a cluster's evolution. This contribution focuses on what we can learn by studying velocity anisotropy and energy equipartition in globular clusters with Hubble Space Telescope proper motions.